My Golden Days = Trois souvenirs de ma jeunesse. [videorecording (DVD)] - Dolmaire, Quentin; Roy-Lecollinet, Lou; Amalric, Mathieu, 1965-; Rabourdin, Olivier, 1959- (Magnolia Home Entertainment, 2016)
The story of Paul Dedalus, an anthropologist preparing to leave Tajikistan. Reflecting on his life, he has a series of flashbacks starting from his childhood in Roubaix; his mother's attacks of madness, his father's alienating depression. He remembers a student trip to the USSR, where a clandestine mission led him to offer up his own identity for a young Russian, whom he considered a phantom twin for the remainder of his life.